Technological knowledge and businesses inter-communication as elements of change in associative management of forest-industry SMEs - Tañski, Nilda Catalina; Jardon, Carlos Maria (Revista de Administração da UFSM, 2018)
This article aims to analyze the behavior and actions of agents related to changes brought about by the emergence of technological knowledge and inter-communication and its effect on organizational change of the SMEs from the Forest-industry sector and related activities, in order to facilitate the association management. To do this, it conducted a qualitative research, conducted in the area of Alto Parana in the province of Misiones, in which data were collected through interviews to twelve entrepreneurs in the Forest-industry and related activities sector. Such information was analyzed using the Atlas ti program version 4.1. Once selected categories of causality effects were studied using a combined method of principal component analysis and qualitative comparative analysis. The results show which are the categories associated with inter-communication and technological knowledge which should operate for short-term organizational change impacts when it is intended to facilitate entry into a process associativity within the sector. The analysis shows that inter-communication has an impact on organizational change. However, technological knowledge is still scarce, and does not show enough evidence to affect organizational change.